RNA Sequencing Analysis of the msl2msl3, crl, and ggps1 Mutants Indicates that Diverse Sources of Plastid Dysfunction Do Not Alter Leaf Morphology Through a Common Signaling Pathway - Luesse, Darron R.; Wilson, Margaret E.; Haswell, Elizabeth S. (Frontiers in Plant Science, 2015)
Determining whether individual genes function in the same or in different pathways is an important aspect of genetic analysis. As an alternative to the construction of double mutants, we used contemporary expression profiling methods to perform pathway analysis on several Arabidopsis thaliana mutants, including the mscS-like (msl)2 msl3 double mutant. MSL2 and MSL3 are implicated in plastid ion homeostasis, and msl2 msl3 double mutants exhibit leaves with a lobed periphery, a rumpled surface, and disturbed mesophyll cell organization. Similar developmental phenotypes are also observed in other mutants with defects in a range of other chloroplast or mitochondrial functions, including biogenesis, gene expression, and metabolism. We wished to test the hypothesis that the common leaf morphology phenotypes of these mutants are the result of a characteristic nuclear expression pattern that is generated in response to organelle dysfunction. RNA-Sequencing was performed on aerial tissue of msl2 msl3 double, geranylgeranyl diphosphate synthase 1 (ggps1), and crumpled leaf (crl) mutants. While large groups of co-expressed genes were identified in pairwise comparisons between genotypes, we were only able to identify a small set of genes that showed similar expression profiles in all three genotypes. Subsequent comparison to the previously published gene expression profiles of two other mutants, yellow variegated 2 (var2) and scabra3 (sca3), failed to reveal a common pattern of gene expression associated with superficially similar leaf morphology defects. Nor did we observe overlap between genes differentially expressed in msl2 msl3, crl, and ggps1 and a previously identified retrograde core response module. These data suggest that a common retrograde signaling pathway initiated by organelle dysfunction either does not exist in these mutants or cannot be identified through transcriptomic methods. Instead, the leaf developmental defects observed in these mutants may be achieved through a number of independent pathways.